Dissimilatory nitrate reduction in urban lake ecosystems: A comparison study between closed and open lakes in Chengdu, China. (1st May 2022) - Yang, Zhanbiao; Lu, Lan; Cheng, Zhang; Xian, Junren; Yang, Yuanxiang; Liu, Lixia; Xu, Xiaoxun
Highlights: Potential rates of DEN, anammox, and DNRA were quantified in UCL and UOL. Functional genes and bacteria community of NO3 − reduction were determined. DEN dominated NO3 − reduction and N-losses in urban lake ecosystem of Chengdu. UOL had high DEN and anammox potential rates and UCL had high DNRA potential rate. Further management should be focused on the urban closed lakes in the future. Abstract: Urban lake ecosystems play important roles in nitrogen cycling, yet the occurrence, contribution and mechanism of nitrate reduction in urban closed and open lakes (UCL and UOL) remain unclear. On November – December of 2020, the potential rates of denitrification (DEN), anammox (ANA), and dissimilatory nitrate reduction to ammonium (DNRA) were quantified using slurries incubations in six urban lakes of Chengdu, China. The environmental variables, genes abundance ( nirS, hzsB and nrfA ), bacterial 16S rRNA gene were also measured. UOL had higher water ammonium (NH4 + ), nitrate (NO3 − ) and nitrite (NO2 − ), and sediment NH4 +, NO3 −, total organic carbon (TOC) and ferrous iron (Fe 2+ ) content than UCL. The potential rates of DEN and anammox in UOL were 2.16- and 3.45-times more than in UCL, respectively. Conversely, the DNRA rate in UCL was 1.20-fold higher than UOL. Higher nirS and hzsB abundance were found in UOL, while higher nrfA abundance occurred in UCL. High-throughput sequencing analysis showed that the relative abundance of DEN bacteria was higher in UOL (2.59–12.30%) than in UCL (1.96–6.70%) at the genus level, while the relative abundance of DNRA bacteria was higher in UCL (2.02–4.19%) than in UOL (1.14–2.31%). The difference in the relative abundance of anammox bacteria at the genus level was not significant. Multiple linear regression showed that the physicochemical properties and nitrate reduction bacteria together control the potential nitrate reduction rates. Since a higher nitrogen retention capability appears in UCL, according to the nitrogen retention index (NRI), further management should be focused on urban closed lakes to avoid the potential for eutrophication. Graphical abstract: Image, graphical abstract